A comprehensive analysis of stable configurations of nonrotating BTZ-ModMax thin-shell wormholes - Faisal Javed; Arfa Waseem; Sobia Sadiq; G. Mustafa (European Physical Journal C: Particles and Fields)
Abstract This paper investigates the characteristics and stability of nonrotating BTZ-ModMax thin-shell wormholes, emphasizing the interaction between spacetime structure and black hole parameters. The locality of the event horizon is substantially affected by the ModMax parameter $$ξ $$ ξ and the horizon shifting inward by increasing the ModMax parameter. We examine that enhancing the charge of a black hole results in an extension of the horizon radius which shows the intricate interplay between charge and geometry. Here, we use different types of matter distribution characterized by distinct equations of state. It is noted that the thin-shell wormhole configurations containing quintessence-like matter have more stability, whereas configurations with phantom energy demonstrate unstable behavior. Our stability analysis reveals that thin-shell wormholes exhibit increased stability with higher values of charge, whereas larger cosmological constants diminish stability regions. Moreover, the generalized Chaplygin gas results in unstable configurations, underscoring the significance of the matter type in ascertaining wormhole stability. These findings deepen our comprehension of thin-shell wormholes and create new possibilities for future inquiry in theoretical physics.